Factors Associated with HIV Viral Suppression Among Transgender Women in Lima, Peru - Rich, Katherine M.; Wickersham, Jeffrey A.; Valencia Huamaní, Javier; Kiani, Sara N.; Cabello, Robinson; Elish, Paul; Florez Arce, Jorge; Pizzicato, Lia N.; Soria, Jaime; Sanchez, Jorge; Altice, Frederick L. (Mary Ann Liebert, 2018)
Purpose: Globally, transgender women (TGW) experience a high burden of adverse health outcomes, including a high prevalence of HIV and sexually transmitted infections (STIs) as well as psychiatric disorders and substance use disorders. To address gaps in HIV research in Peru focused specifically on TGW, this study presents characteristics of a sample of HIV-positive TGW and identifies factors associated with viral suppression. Methods: Between June 2015 and August 2016, 50 HIV-positive TGW were recruited in Lima, Peru. Multivariable logistic regression was used to identify factors associated with viral suppression (<200 copies/mL) among the TGW. Results: Among TGW, 85% achieved viral suppression. Approximately half (54%) reported anal sex with more than five partners in the past 6 months, 38% reported sex work, 68% had not disclosed their HIV status to one or more of their partners, and 38% reported condomless sex with their last partner. The prevalence of alcohol use disorders was high (54%), and 38% reported use of drugs in the past year. Moderate-to-severe drug use significantly reduced odds of achieving viral suppression (adjusted odds ratio 0.69; 95% confidence interval: 0.48-0.98). Conclusion: Our findings highlight the need for integrated treatment for substance disorders in HIV care to increase the viral suppression rate among TGW in Lima, Peru.